2022
DOI: 10.3390/ijerph19137552
|View full text |Cite
|
Sign up to set email alerts
|

Number of Bacteria in Saliva in the Perioperative Period and Factors Associated with Increased Numbers

Abstract: Perioperative oral management is performed to prevent postoperative complications, but its indication and management method are unclear. This study aimed to investigate salivary bacterial counts pre-and postoperatively, and factors related to increased bacterial count postoperatively. We included 121 patients who underwent surgery under general anesthesia and perioperative oral management. The bacterial count in saliva was determined preoperatively, and first and seventh days postoperatively using the dielectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…This is in line with previous studies comparing conducted by Pathak et al 14 Poor oral hygiene can have detrimental effects on intraoral wound healing and is associated with a risk of surgical site infection. 18,19 However, the results of this study differ from those of Hamid et al who reported no significant difference in oral hygiene (measured by GI scores) between screw-retained and Erich's arch bar. 20 Whichever modality of achieving MMF is chosen, the treatment of facial fractures should not be compromised.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in line with previous studies comparing conducted by Pathak et al 14 Poor oral hygiene can have detrimental effects on intraoral wound healing and is associated with a risk of surgical site infection. 18,19 However, the results of this study differ from those of Hamid et al who reported no significant difference in oral hygiene (measured by GI scores) between screw-retained and Erich's arch bar. 20 Whichever modality of achieving MMF is chosen, the treatment of facial fractures should not be compromised.…”
Section: Discussioncontrasting
confidence: 99%
“…The impact of development of DM and infectious complications in DM patients on hospitalization costs has also been frequently reported [23][24][25] . In other studies, oral bacterial infection and poor oral health were shown to be risk factors related to surgical site infection after various cancer and cardiovascular surgical procedures 9,[26][27][28][29] , while a relationship between oral microbial colonization and ventilator-associated pneumonia in patients in intensive care units has also been reported 30,31 . In other reports, oral bacteria were shown to be associated with onset of aspiration pneumonia after cancer surgery [32][33][34] .…”
Section: Discussionmentioning
confidence: 91%
“…It is important to reduce the number of bacteria in saliva, prevent aspiration, and improve the general condition of the patient to prevent aspiration pneumonia. Therefore, the importance of oral care for older adults and postoperative patients is widely reported [1][2][3][4][13][14][15][16][17]. Additionally, VAP in endotracheally intubated patients is directly related to survival outcomes and is a serious post-operative complication [6].…”
Section: Discussionmentioning
confidence: 99%
“…The human oral cavity contains many microorganisms (such as bacteria and fungi) that are controlled by oral cleansing methods such as oral intake, saliva secretion, and swallowing. However, bacterial counts are markedly increased in older adults with decreased oral functions, such as in cases of tongue pressure [ 1 ], fasting, or tube feeding [ 2 ], and in intubated patients [ 3 , 4 ]. The most effective method to reduce the oral bacterial count is rinsing the mouth, which is not possible in patients with decreased swallowing function or under intubation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%